ASSESSMENT OF THE LEVEL OF CONCERNS REGARDING COVID-19 PANDEMIC AMONG HOSPITAL BASED HEALTHCARE WORKERS IN QUETTA, PAKISTAN - Zia, Anjum; Ahmad, Farah; Ali, Akhtar (Infectious Diseases Journal of Pakistan, 2023)
Background: The study was aimed to assess the level of concerns regarding the COVID-19 Pandemic among hospital-based healthcare workers in Quetta, Pakistan. Material and Methods: It was a cross-sectional study carried out between August to December 2020 among frontline healthcare workers who work in the emergency department of different public sector hospitals of Quetta. The questionnaire was distributed through online social forums and physically at some places. The calculated sample size was n=400. Results: The most significant findings were that n=179 (44.8%) felt themselves at risk to get Covid 19 from workplace; n=168 (42%) respondents had limited their social activities; n=125 (58.14%) respondents had access to complete Personnel Protective Equipment (PPEs) n=290 (72.5%) cumulative respondents had access to some -PPE items. Conclusion: The healthcare workers suffered much mental anguish, trauma and isolation during the covid-19 pandemic. Scarcity of resources preventing access to complete PPE further added to it. Key Words: Covid-19, Concern, Healthcare workers, Quetta